Climate change and the resurgence of malaria in the East African highlands. - Hay, S; Cox, J; Rogers, D; Randolph, SE; Stern, D; Shanks, G; Myers, M; Snow, R (2002)
The public health and economic consequences of Plasmodium falciparum malaria are once again regarded as priorities for global development. There has been much speculation on whether anthropogenic climate change is exacerbating the malaria problem, especially in areas of high altitude where P. falciparum transmission is limited by low temperature. The International Panel on Climate Change has concluded that there is likely to be a net extension in the distribution of malaria and an increase in incidence within this range. We investigated long-term meteorological trends in four high-altitude sites in East Africa, where increases in malaria have been reported in the past two decades. Here we show that temperature, rainfall, vapour pressure and the number of months suitable for P. falciparum transmission have not changed significantly during the past century or during the period of reported malaria resurgence. A high degree of temporal and spatial variation in the climate of East Africa suggests further that claimed associations between local malaria resurgences and regional changes in climate are overly simplistic.